Encoding Ecological Knowledge through Honey Naming: An Onomastic and Ecolinguistic Study of Baduy Honey - Nadhifa Indana Zulfa Rahman; Liliana Muliastuti; Siti Ansoriyah; Ayu Puspa Nanda; Wita Septiani Rahmaputri; Sintowati Rini Utami (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study investigates the naming system of Baduy honey varieties as a linguistic mechanism for encoding and transmitting ecological knowledge. Drawing on primary data comprising 23 honey names collected through online documentation and secondary literature, the study applies three theoretical frameworks: onomastics, ecolinguistics (Stibbe, 2015), and frame semantics (Fillmore, 1982). The analysis identifies five principal naming patterns: bee-based naming, flora-based naming, place-based naming, sensory-based naming, and quality-based naming. The findings reveal that each honey name encodes a salient ecological attribute selected from a broader set of environmental knowledge, activating an ecological frame that encompasses knowledge about bee species, nectar sources, landscape, and harvesting practices. Building on these findings, this study introduces the concept of Ecological Frame Encoding (EFE), defined as the linguistic process through which a community selects the most ecologically salient attribute of an environmental entity, evokes the corresponding ecological frame, and encodes it into a stable name that facilitates the preservation and intergenerational transmission of local ecological knowledge. This study contributes to the fields of ecological onomastics and ecolinguistics by demonstrating that Baduy honey names are not merely commercial labels but function as ecological frames that archive local environmental memory.